2019
DOI: 10.1016/j.antiviral.2019.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a clinical compound losmapimod that blocks Lassa virus entry

Abstract: A B S T R A C TLassa virus (LASV) causes Lassa hemorrhagic fever in humans and poses a significant threat to public health in West Africa. Current therapeutic treatments for Lassa fever are limited, making the development of novel countermeasures an urgent priority. In this study, we identified losmapimod, a p38 mitogen-activated protein kinase (MAPK) inhibitor, from 102 screened compounds as an inhibitor of LASV infection. Losmapimod exerted its inhibitory effect against LASV after p38 MAPK down-regulation, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 38 publications
1
19
0
1
Order By: Relevance
“…In addition, we observed a reduction in viral E1 protein expression, suggesting that p38 might serve as a therapeutical target to control MAYV infection. Zhang and collaborators showed that Losmapimod is able to inhibit Lassa virus entry, although through a mechanism not involving p38 inhibition [ 58 ]. In another study, Losmapimod was shown to disrupt SARS-CoV-2 replication in a model of primary alveolar epithelial cells, suggesting that p38 is a potential target for COVID-19 treatment [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we observed a reduction in viral E1 protein expression, suggesting that p38 might serve as a therapeutical target to control MAYV infection. Zhang and collaborators showed that Losmapimod is able to inhibit Lassa virus entry, although through a mechanism not involving p38 inhibition [ 58 ]. In another study, Losmapimod was shown to disrupt SARS-CoV-2 replication in a model of primary alveolar epithelial cells, suggesting that p38 is a potential target for COVID-19 treatment [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Drug screens have identified small molecules with activity against LASV and other arenaviruses. Most are investigational drugs and include clotrimazole derivatives ( 7 ), ST-193 ( 8 , 9 ), F3406 ( 10 ), LHF-535 ( 11 ), kinase inhibitors ( 12 , 13 ), losmapimod ( 14 ), and inhibitors of purine and pyrimidine biosynthesis ( 15 17 ). The polymerase inhibitors remdesivir and favipiravir have shown some activity against arenaviruses in cell cultures ( 18 ) and in vivo ( 19 ), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we observed a reduction in viral E1 protein expression, suggesting that p38 might be to a therapeutical target to control MAYV infection. Zhang and collaborators showed that Losmapimod is able to inhibit Lassa virus entry, although through a mechanism not involving p38 inhibition [57]. In another study, Losmapimod was shown to disrupt SARS-CoV-2 replication in a model of primary alveolar epithelial cells, suggesting that p38 is a potential target for COVID-19 treatment [58].…”
Section: Discussionmentioning
confidence: 99%